-16(y+1)+5(4y-4)=3(y-3)+10

Simple and best practice solution for -16(y+1)+5(4y-4)=3(y-3)+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16(y+1)+5(4y-4)=3(y-3)+10 equation:


Simplifying
-16(y + 1) + 5(4y + -4) = 3(y + -3) + 10

Reorder the terms:
-16(1 + y) + 5(4y + -4) = 3(y + -3) + 10
(1 * -16 + y * -16) + 5(4y + -4) = 3(y + -3) + 10
(-16 + -16y) + 5(4y + -4) = 3(y + -3) + 10

Reorder the terms:
-16 + -16y + 5(-4 + 4y) = 3(y + -3) + 10
-16 + -16y + (-4 * 5 + 4y * 5) = 3(y + -3) + 10
-16 + -16y + (-20 + 20y) = 3(y + -3) + 10

Reorder the terms:
-16 + -20 + -16y + 20y = 3(y + -3) + 10

Combine like terms: -16 + -20 = -36
-36 + -16y + 20y = 3(y + -3) + 10

Combine like terms: -16y + 20y = 4y
-36 + 4y = 3(y + -3) + 10

Reorder the terms:
-36 + 4y = 3(-3 + y) + 10
-36 + 4y = (-3 * 3 + y * 3) + 10
-36 + 4y = (-9 + 3y) + 10

Reorder the terms:
-36 + 4y = -9 + 10 + 3y

Combine like terms: -9 + 10 = 1
-36 + 4y = 1 + 3y

Solving
-36 + 4y = 1 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-36 + 4y + -3y = 1 + 3y + -3y

Combine like terms: 4y + -3y = 1y
-36 + 1y = 1 + 3y + -3y

Combine like terms: 3y + -3y = 0
-36 + 1y = 1 + 0
-36 + 1y = 1

Add '36' to each side of the equation.
-36 + 36 + 1y = 1 + 36

Combine like terms: -36 + 36 = 0
0 + 1y = 1 + 36
1y = 1 + 36

Combine like terms: 1 + 36 = 37
1y = 37

Divide each side by '1'.
y = 37

Simplifying
y = 37

See similar equations:

| 4q+2=3q-2 | | 57.99-0.11d=58.54 | | 28x-4+6-15x-12x-20=-6 | | 7b+2b=63 | | 2x+15=3x+110 | | 5(7+w)=4(6+w) | | 12a^3x^2-6a^2x^4/6a^3x^2 | | 10(3x-2)=5(2-x) | | -3(x+5)=5x-(3+2x) | | t-7= -7 | | 4(6-x)=10 | | 4k=76 | | m=n/16 | | 17x-(7x-5)-(7000-20000)-49000=0 | | y=(6x+1)(x-5) | | 5(3c+2)+4(2c+1)= | | 4x-3=4x-5 | | 7.2x+2=6.2x | | 15f=k(k-f)+7+8f | | 1x+45=2x-2 | | (40x+16/6)/(20x+8/6x) | | 88=n+81 | | u+32=99 | | 0.091=1-z | | -20p+10=-19p-19 | | y^8*y^15= | | 7q=84 | | 4.7d=6.11 | | -20p+10p=-19p-19 | | 5.6-0.32s=1.12 | | 16.15=w+3 | | y+3.33=14.33 |

Equations solver categories